Le Chaebol après la crise financière de 1997 - Chung-Yeol Park (Revue de la Régulation)
The Chaebol after the 1997. Financial Crisis Changes and Continuity. The paper presents the changes undergone by the Korean Chaebols after the financial crisis of 1997. The first section shortly recalls the history of the birth and development of the Chaebols and presents their specific organizational traits.  The second and third sections are dedicated to the presentation of the financial reforms and of the reforms of the enterprises implemented in Korea after 1997. The fourth section presents two cases studies of the changes introduced after 1997 on two major chaebols : Hyundai Group and Samsung Group. These case studies and other more general empirical data are used to evaluate both the changes and the continuity in Chaebol’s organizational forms and behaviours after the 1997 crisis.